(untitled) (Academic Journal of Internal Affairs, 2021)
The study presents the tasks and the system of the Court of Honor, which has been introduced at law enforcement agencies since 2016, and the authors - based on their personal professional experiences - evaluate the first five years’ operation of the legal institution.